Problem-Based Learning Integrated Reading and Writing in Work and Energy Phenomena: Its Effectiveness on Problem-Solving Skills and Reading-Writing Literacy - Safitri, Indah; Sinaga, Parlindungan; Suhendi, Endi (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2022)
Problem-solving Skills and Reading-Writing Literacy are two necessary things students must have to compete in the 21st century. This study aims at determining the effectiveness of Problem-based Learning with Integrated Reading and Writing tasks to improve students' problem-solving and reading-writing literacy skills. A quantitative method using a quasi-experimental design with a non-equivalent control group was employed in this study. The sampling technique used in this study was the purposive sampling technique. The sample used in this study was 36 students divided into two groups: the control group and the experimental group. The instrument used in this study was a physics problem-solving skill test instrument and a reading-writing literacy instrument. The data analysis technique in this study was a quantitative analysis technique. The results showed that the N-gain value of the physics problem-solving skill test for the experimental group was 0.67 in the medium category, and the control group was 0.65 in the medium category. In the reading-writing literacy test, the N-gain value for the experimental group was 0.55 in the medium category and 0.29 in the low category for the control group. The Problem-based Learning model with Integrated Reading and Writing Tasks has little impact on improving students' problem-solving skills. However, it has a significant effect on increasing students' reading-writing literacy.